How does one health fit into current academic frameworks? Insights from a SWOT analysis by the North America One Health University Network - Berrian, Amanda M., author; Ferrara, James, author; Matos, Alice, author; Carmichael, K. Paige, author; Woods, Christopher W., author; Thakur, Siddhartha, author; Goldstein, Tracey, author; Frontiers, publisher (Colorado State University. Libraries, 2025)
Introduction: One Health (OH) has gained support by health organizations, academics, and policymakers worldwide. To advance the approach across its broad use categories, workforce development has been a focus area, resulting in many versions of recommendations for OH core competencies and a multitude of training programs at various learner levels. Questions remain about strengths (and weaknesses) of available programs and employment prospects for graduates. Methods: At the inaugural meeting of the North America One Health University Network (NAOHUN) in 2024, over 90 university and partner agency representatives discussed these questions through a workshop-based SWOT analysis, describing strengths (S), weaknesses (W), opportunities (O), and threats (T) facing OH education programs. Participants were grouped according to the program type offered by their organization: professional, graduate, undergraduate, micro-credential, non-degree program, as well as no current offering. Participants recorded their inputs on a collaborative web-based platform which were then exported and analyzed using thematic analysis. Results: Discussions helped to elucidate internal and external factors that both help and hinder the design and delivery of OH education. Insights indicate that the number and diversity of OH educational programs have increased over time as has the interest from prospective trainees. Challenges remain, however, in program administration, maintaining collaborations, and marketing of skills to employers. Conclusion: These discussions will help to ensure sustainability and relevance of OH training programs. With the launch of NAOHUN, these insights will provide strategic direction for establishing universally accepted OH education competencies and other priority initiatives for network members.
Keywords: One Health; workforce development; education; core competencies; curriculum; training; SWOT analysis